Migration patterns of Greenland halibut in the North Atlantic revealed by a compiled mark–recapture dataset. (18th July 2022) - Vihtakari, Mikko; Elvarsson, Bjarki Þór; Treble, Margaret; Nogueira, Adriana; Hedges, Kevin; Hussey, Nigel E; Wheeland, Laura; Roy, Denis; Ofstad, Lise Helen; Hallfredsson, Elvar H; Barkley, Amanda; Estévez-Barcia, Daniel; et al.
Abstract: Marine fisheries are often allocated to stocks that reflect pragmatic considerations and may not represent the species' spatial population structure, increasing the risk of mismanagement and unsustainable harvesting. Here we compile mark–recapture data collected across the North Atlantic to gain insight into the spatial population structure of Greenland halibut ( Reinhardtius hippoglossoides ), an issue that has been unresolved for decades. The dataset contains 168130 fish tagged from 1952 to 2021, with 5466 (3.3%) recaptured individuals. Our results indicate that fish tagged at <50 cm body length migrate at higher rates, suggesting that mark–recapture studies on adult individuals underestimate population-level migration rates. We find evidence for migrations across management units in the North Atlantic indicating two regional offshore populations: one in the Northeast Atlantic, where the West Nordic and Northeast Arctic stocks, currently managed separately, likely belong to a single population that spans from the Kara Sea to Southeast Greenland; and one in the Northwest Atlantic where migration was observed between the Newfoundland and Labrador stock and the Northwest Arctic stock in Davis Strait and Baffin Bay. Our findings indicate complex population structure with implications for international and domestic fisheries management of this long-lived species.